Legal Protection in the Form of Restitution of Victims of Severe Abuse Linked to Child Protection Law (Case Study of David Ozora) - Bajaber, Nadira Umar; Yuli Wahyuningsih, Yuliana (Law Development Journal, 2025)
The legal protection in the form of restitution for child victims of serious abuse, highlighting the case of David Ozora as a concrete study. The main focus is directed at the inequality of the criminal justice system, which tends to be perpetrator-oriented, while the position of the victim is often neglected. Restitution is seen as an important instrument in realizing restorative justice that emphasizes the restoration of victims' rights, not only through criminal sanctions for the perpetrators. This study uses a normative juridical method, combining a legislative approach and case studies. The research findings indicate that legal protection for child victims has been regulated through the Child Protection Law, the Witness and Victim Protection Law, and Government Regulation Number 43 of 2017, which specifically regulates the procedures for granting restitution. In the case of David Ozora, the court not only sentenced the perpetrator to prison but also determined a large amount of restitution, indicating the state's recognition of the victim's right to restitution. However, the application of excessively high restitution also creates a dilemma when the perpetrator is a child, as it has the potential to conflict with the principles of restorative justice in the juvenile criminal justice system. Thus, this study emphasizes the importance of implementing proportional restitution that prioritizes the best interests of children, both as victims and perpetrators, to achieve substantive justice consistent with humanitarian values.